2016
DOI: 10.1007/s00449-016-1566-0
|View full text |Cite
|
Sign up to set email alerts
|

A facile and efficient method of enzyme immobilization on silica particles via Michael acceptor film coatings: immobilized catalase in a plug flow reactor

Abstract: A novel method was developed for facile immobilization of enzymes on silica surfaces. Herein, we describe a single-step strategy for generating of reactive double bonds capable of Michael addition on the surfaces of silica particles. This method was based on reactive thin film generation on the surfaces by heating of impregnated self-curable polymer, alpha-morpholine substituted poly(vinyl methyl ketone) p(VMK). The generated double bonds were demonstrated to be an efficient way for rapid incorporation of enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Catalase activity was monitored by observing the rate of decomposition of hydrogen peroxide using a spectrophotometer UV -VIS JASCO V -530. Absorbance of H 2 O 2 was measured at a wavelength of 240 nm (Bayramoglu et al, 2016). From the change of the concentration of hydrogen peroxide in the time from 0 s to 15 s, which has a linear relationship, the values of reaction rate constant were determined.…”
Section: Reagentsmentioning
confidence: 99%
“…Catalase activity was monitored by observing the rate of decomposition of hydrogen peroxide using a spectrophotometer UV -VIS JASCO V -530. Absorbance of H 2 O 2 was measured at a wavelength of 240 nm (Bayramoglu et al, 2016). From the change of the concentration of hydrogen peroxide in the time from 0 s to 15 s, which has a linear relationship, the values of reaction rate constant were determined.…”
Section: Reagentsmentioning
confidence: 99%
“…The Km values of both immobilized enzymes were higher than the value of the free enzyme while the Vmax values were lower. There are many studies in the literature reporting that CAT activity is greatly reduced after immobilization (Ozyilmaz et al, 2007;Çorman et al, 2010;Alptekin et al, 2010;Bayramoglu et al, 2016;Barreca et al, 2018). In this study, Vmax/Km values, which are an indicator of the catalytic efficiency after immobilization, were determined as 28 % and 39.2 % of the free enzyme for ChiGAL-CAT and ChiGAL-pLYSGAL-CAT, respectively.…”
Section: Resultsmentioning
confidence: 71%
“…Sel et al (2021) immobilized the CAT enzyme to P (MMA-co-PEG500MA) gel and reported that it retained 21% of the initial activity after 20 uses. Bayramoglu et al (2016) found that after 10 uses of catalase immobilized on silica-based support, there was a 23% decrease in activity compared to first activity value. Arabacı & Usluoğlu (2012) covalently immobilized catalase onto chitosan carrier via glutaraldehyde and determined that it preserved 70% of its initial activity after 10 uses.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Magnetic nanoparticles (MNPs) have been demonstrated to be extremely applicable for immobilized enzyme recycling, because of their easy separation, low mass-transfer resistance, larger surface area, and high enzyme loading capacity. The attachment between enzymes and nanoscale carriers for immobilization could be classified as adsorption, covalent bond, and encapsulation. Compared to adsorption and encapsulation, covalent binding could efficiently prevent the leak of enzymes, and thus immobilized enzymes would be more reusable. However, the irreversible covalent binding is usually short of specific recognition, and the harsh binding conditions would lead to the denaturation of immobilized enzymes. Those restrictions could be overcome by employing biomolecule recognition to achieve the interaction of supports and enzymes. The specific interaction between glycan-specific proteins and carbohydrates could achieve the specifically conjunction without altering the structure of enzymes. , Concanavalin A (ConA), isolated from Canavalia ensiformis , is a representative of plant lectin from the superfamily of glycan-specific receptor with conserved sequences and typical structure. , Until now, ConA has been widely used in cancer diagnostics, affinity chromatography, , and glycoproteins isolation. , Moreover, several studies have revealed that ConA could work as a promising biomolecule linker to develop novel immobilization methods. ,, …”
Section: Introductionmentioning
confidence: 99%